ENVIRONMENTAL MANAGEMENT IN CROSS-BORDER REGIONS OF THE COUNTRIES OF THE EURASIAN ECONOMIC UNION (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The EAEU Treaty is the main regulatory legal act regulating the relations of the member states of the Eurasian Economic Union (hereinafter referred to as the EAEU). The treaty presents certain elements of environmental regulation of relations between the countries. The assessment of the degree of interaction of the Russian Federation with the EAEU countries in the field of cross-border nature management indicates the need for a systematic approach in the organization of natural resources management. Despite significant progress in solving a number of problems in the EAEU countries, the creation of a new format of interstate interaction should intensify the development of integrated strategies to achieve sustainable environmental management in cross-border territories.
Keywords: Eurasian Economic Union; environmental management; cross-border region